3D microstructure reconstruction of chrome carbide weld overlays. (November 2014) - Barnes, N.; Borle, S.; Dewar, M.; Andreiuk, J.; Mendez, P. F.
Abstract : This paper addresses a current debate about the morphology of M7 C3 phase in the chrome carbide overlay (CCO) and white iron community. This morphology was investigated using a serial sectioning technique in combination with computer post-processing software. A 600×600×300 μm volume of CCO was reconstructed in three dimensions (3D) to determine the difference between blade and rod-like carbide morphologies. The 3D analysis revealed that the two carbides morphologies correspond to the same hexagonal rod-like structures, but are oriented in different directions relative to the sectioning plane.